2021
DOI: 10.3390/nano11040927
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Sintering-Bonding Technology Using Ag Nanoparticles for Electronic Packaging

Abstract: Metal nanoparticles (NPs) have attracted growing attention in recent years for electronic packaging applications. Ag NPs have emerged as a promising low-temperature bonding material owing to their unique characteristics. In this study, we mainly review our research progress on the interconnection of using polyol-based Ag NPs for electronic packaging. The synthesis, sintering-bonding process, bonding mechanism, and high-temperature joint properties of Ag NP pastes are investigated. The paste containing a high c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…In addition, it should be noted that such a stage transition in oxygen was accomplished at a temperature below 250 °C, when the decomposition of PVP had not yet begun according to the thermal analysis results shown in Figure 2 . As reported by Yan et al [ 51 ], the organic dispersant in silver NP ink had an important influence on the sintering process, because it was found through FTIR that the carboxyl oxygen atoms of PVP interacted with silver NPs on the surface. When the temperature was low, the particles were encapsulated by PVP, and the sintering mechanism at this time depended on surface diffusion; when the temperature was raised to decompose the dispersant, the sintering process turned to volumetric diffusion.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In addition, it should be noted that such a stage transition in oxygen was accomplished at a temperature below 250 °C, when the decomposition of PVP had not yet begun according to the thermal analysis results shown in Figure 2 . As reported by Yan et al [ 51 ], the organic dispersant in silver NP ink had an important influence on the sintering process, because it was found through FTIR that the carboxyl oxygen atoms of PVP interacted with silver NPs on the surface. When the temperature was low, the particles were encapsulated by PVP, and the sintering mechanism at this time depended on surface diffusion; when the temperature was raised to decompose the dispersant, the sintering process turned to volumetric diffusion.…”
Section: Discussionmentioning
confidence: 87%
“…The temperatures of the initiation of PVP decomposition were about 280 °C in oxygen and 400 °C in nitrogen, respectively, as shown in Figure 2 . As suggested in the related literature [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ], the encapsulation of silver NPs by organic dispersants significantly affects the sintered morphology and consequently the properties of sintered silver thin films. Thus, it could be supposed that the breaching of the PVP dispersant capsulation of the silver NPs through enabling its decomposition is a prerequisite condition for the stage transition from particle coalescence to film densification, because the presence of PVP would limit the volumetric diffusion of silver NPs.…”
Section: Discussionmentioning
confidence: 99%
“…Metal nanoparticles (NPs) have recently gained popularity due to their unique properties such as low melting temperature and high diffusion coefficient [ 91 ]. Research has shown that epoxy conductive adhesives enhance their heat conductivity when integrated with metal fillers.…”
Section: Adhesives With Improved Conductivitymentioning
confidence: 99%
“…Ag nanoparticles are widely used as lead-free die attachments due to their relatively high conductivity, superior fatigue properties, and high melting point [ 9 , 10 , 11 ]. However, the high sintering temperature (~250 °C) and long sintering time (30~60 min) associated with their production limit their widespread application [ 12 ].…”
Section: Introductionmentioning
confidence: 99%